Perencanaan Strategis Arsitektur Enterprise SI/TI (Studi Kasus PT Trakindo Utama) - Shedriko Shedriko (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
With the decreased economic activities in mining and oil industries and the fierce competition in heavy equipment industry, PT Trakindo Utama (PTTU) intendsto restructure its company, particularly its information technology development that canfully support its business and improve its service to customers which is the objective of this journal. To restructurethe technology supporting those two matters definitely needs strategic and thoughtful planning. Then, Enterprise Architecture Planning methodology is choosen to providean enterprise-scale solution to those matters. The result of the planningincludes data, application and technology architecture planning and the technical aspects of its implementation. This journal is expected to provide an alternative solution to PTTU in doing strategic planning appropriate and useful for the company in the future.